Reticulated platelets - Clinical application and future perspectives - Meintker, Lisa; Krause, Stefan (Journal of Laboratory Medicine, 2020)
Reticulated platelets are immature platelets freshly released from the bone marrow into the circulation and contain vestigial amounts of ribonucleic acid. Thus, they can serve as an indicator for the activity of thrombopoiesis. Despite the current lack of a standardized reference method, two types of hematology analyzers have incorporated a fully automated measurement of reticulated platelets. The "immature platelet fraction" (IPF; Sysmex XE-/XN-series) has some clinical utility in the differential diagnosis of thrombocytopenia. This is less clear for "reticulated platelets" (retPLT; Abbott CELL-DYN Sapphire/Alinity HQ). The usefulness of these parameters in the prediction of platelet recovery after chemotherapy or stem cell transplantation and as a decision aid for platelet transfusions has not been unequivocally confirmed. Recent findings have shown an association of reticulated platelets with an adverse risk in patients with coronary artery disease and stroke as well as resistance to anti-platelet therapy. Furthermore, a role of reticulated platelets for the prediction of sepsis was indicated. However, validation in larger prospective trials is necessary to establish the clinical benefit of reticulated platelets in these conditions. This review gives an overview of the available analytical methods and summarizes the current knowledge regarding the clinical application of reticulated platelets.
CRIS-Team Scopus Importer:2020-02-28
Keywords: immature platelets; IPF; reticulated platelets